2018
DOI: 10.1016/j.atherosclerosis.2018.06.882
|View full text |Cite
|
Sign up to set email alerts
|

Dietary 23–hydroxy ursolic acid protects against atherosclerosis and obesity by preventing dyslipidemia-induced monocyte priming and dysfunction

Abstract: Dietary 23-OHUA reduces weight gain and attenuates atherogenesis in mice by protecting monocytes against metabolic stress-induced priming and dysfunction. Based on its mechanism of action, 23-OHUA may represent a novel therapeutic approach for the prevention and treatment of obesity and atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…Protective effect against diabetic nephropathy[201]h. Reducer of weight gain and atherosclerosis[202]Alpha-pinenea. Antibacterial[203]b.…”
Section: Introductionmentioning
confidence: 99%
“…Protective effect against diabetic nephropathy[201]h. Reducer of weight gain and atherosclerosis[202]Alpha-pinenea. Antibacterial[203]b.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the pharmacokinetics of UA, several groups have studied the compounds’ toxicity as well as that of many of its naturally occurring analogues. Our group demonstrated in human THP-1 cells that at concentrations below 30 μM, UA and ten of its naturally occurring analogues did not exhibit any significant toxicity [ 19 ]. Using a brine shrimp bioassay, Somova et al showed that UA had no toxic effects on mice when they administered UA for 5 days at 60 mg/kg of body weight [ 20 ].…”
Section: Bioavailability and Pharmacokineticsmentioning
confidence: 99%
“…Ursolic acid (UA; 3β‐hydroxy‐urs‐12‐en‐28‐oic acid; Figure 1) is a pentacyclic triterpene consisting of C‐28 carboxylic acid and C‐3 hydroxyl groups are commonly found in fruits, spices, and herbs such as apple, thyme, cranberries, Sambucus nigra leaves and bark, the leaves and flowers of hawthorn, and coffee leaves (Hussain et al., 2017). UA has been reported for its medicinal properties which include anticancer (Kassi et al., 2007; Zhang et al., 2016), anti‐hyperglycemia (Wu et al., 2014), and anti‐obesogenic activities (Nguyen et al., 2018). Its neuroprotective effect has been demonstrated by its ability to modulate nrf2 pathway in cerebral ischemia in mice (Li et al., 2013).…”
Section: Introductionmentioning
confidence: 99%